A Possible Role of Aquaporin Water Channels in Blood Cell Migration in Spleen; Interaction with Cluster of Differentiation Molecules - Thangavelu, Manoj G Tyagi* and Premkumar (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: Aquaporins (AQPs) are molecular water channels that play important physiological roles in fluid transporting organs. The expression and function of AQPs in the immune system are largely unknown. CD11(a―d)/CD18 integrins are adhesion molecules expressed on leukocytes, which play a critical role in leukocyte adhesion, migration and host defense. In the present study, we suggest that the expression of aquaporin water channels on spleen CD positive cells, and the content of CD positive splenocytes in aquaporin may regulate the migration of blood cells. Recent studies and their analysis suggested remarkably decreased monocyte/macrophage subpopulation and significantly decreased granulocyte subpopulation. This is the first hypothetical report suggesting an important role of AQP in the trafficking of hemapoietic cells. <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Key words: Aquaporin, Spleen, Lymphocytes, CD147, Erythrocytes Department of Pharmacology, Christian Medical College, Vellore 632002, Tamilnadu, India Please Cite This Article As: Manoj G Tyagi and Premkumar Thangavelu. 2010. A Possible Role of Aquaporin Water Channels in Blood Cell Migration in Spleen; Interaction with Cluster of Differentiation Molecules. J. Exp. Sci. 1(4):41-42.